Development and application of recombinase polymerase amplification assay for rapid detection of Blastocystis sp. - Xuefang Mei; Changwei Su; Shanrui Zhang; Luwei Jia; Zhenke Yang; Xiaowei Tian; Zhenchao Zhang; Shuai Wang (Parasitology, 2023)
Blastocystis sp. is a common parasite in the intestinal tract of humans and animals. The clinical diagnosis of Blastocystis sp. mainly depends on the microscopic observation of parasite, which can lead to false-negative results. An accurate and convenient diagnostic approach for Blastocystis sp. infection is crucial for effectively preventing and controlling blastocystosis. Herein, we developed a recombinase polymerase amplification (RPA) method for detecting Blastocystis sp. The results showed that the DNA amplification by RPA established in this study could be performed within 5 min at 37°C, with maximum band intensity observed at 30 min. The minimum detection limit of RPA was 100 fg μL−1, consistent with conventional polymerase chain reaction (cPCR). Furthermore, the RPA method exhibited no cross-reactivity with 7 other non-target pathogens in the intestinal tract. Next, the newly established RPA method was used to analyse 40 fecal samples collected clinically, and the detection results were consistent with cPCR. These results corroborate that the newly developed RPA method has good sensitivity and specificity and offers the advantage of short detection times, which can be harnessed for differential diagnosis and rapid detection of Blastocystis sp.